Performance of steers supplemented with protein salts on native pastures - Knorr, Marcelo; Patino, Harold Ospina; da Silveira, André Luís Finkler; Mühlbach, Paulo Roberto Frenzel; Mallmann, Giovanni Matheus; Medeiros, Fabio Schuler (Pesquisa Agropecuaria Brasileira, 2005)
<!--[if gte mso 9]> Normal 0 <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> The objective of this work was to evaluate the effect of protein salts supplementation on performance of beef steers grazing differed native pasture in Rio Grande do Sul State, Brazil. Protein salts were supplemented with: urea, starea, starea plus yeast, and mineral salt. The experiment was conducted during 118 days, and utilized 8 paddocks with 7.5 ha each one, with 8 steers averaging 264 kg and 18 months old, in a completely randomized design. Average composition of pasture was 6.8% of crude protein, 73.3% of neutral detergent fiber, and 42.5% in vitro organic matter digestibility; significative differences weren't detected among treatments. Average daily weight gain of animals fed protein salt with starea plus yeast (0.287 kg), was higher than the weight gain of animals fed mineral salt (0.019 kg); differences weren't detected among urea (0.159 kg) and starea (0.124 kg). Daily intake of protein supplements (0.400 kg) was higher than that of mineral supplement (0.038 kg). Addition of live yeast to the protein salt formulated with starea resulted in better performance of steers grazing differed native pasture.